Professional Educational Institutions Theoretical and Practical Basis of Development of the Content of Pedagogical Activity of Teachers of "Information and Information Technologies" - Juraev Muzaffarjon Mansurjonovich (Zien Journals, 2022)
In this article, the theoretical and practical basis of improving the content of the pedagogical activity of teachers of "Informatics and Information Technologies" of professional educational institutions in the conditions of informatization of education, the state of professional training of teachers, existing problems and solutions, the principles and content of the subject are discussed.
Keywords: information; methodological support; principles; competence